A nano-composite aluminized agent composed of a gallium-aluminum alloy and a three-dimensional porous oxide, and a preparation method and application thereof
Patent Information
- Application Number
- CN202411314948.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-09-20
AI Technical Summary
[0003]为了克服上述现有技术中存在的不能完全满足对纳米钠容易氧化、铝热组分均匀性和分散性精准调控的要求的缺点和不足,本发明的首要目的在于提供了一种由镓铝合金和三维多孔氧化物构成的纳米复合铝热剂的制备方法;该方法通过组分调控和结构设计开发新型铝热剂,通过引入液态金属镓抑制铝燃料表面完整且均一的Al2O3钝化层的产生,同时结合不同的三维多孔氧化剂的限域作用,保护纳米铝的活性,增强铝热组分接触程度和缩短传质扩散长度,从而获得高性能铝镓基纳米复合铝热剂
[0021](1)镓铝基合金用于铝热组分具有改变铝的微观形貌和将部分Al-Al界面转化为Al-Ga界面从而抑制表面完整且均一的Al2O3钝化层的产生的效果,可以避免在处理和储存过程中铝燃料被氧化,又可以加速铝参与反应,从而提高铝的反应活性。另一方面,室温液态金属镓(熔点仅为29.76℃)与金属铝形成的低熔点合金可在较低温度的加热过程中熔化成液态,在熔融灌注过程中三维多孔氧化剂的空间限域作用下能有效抑制铝燃料的尺寸,且能阻止纳米铝在后续过程中发生团聚。
Smart Images

Figure HDA0005051898350000011
Abstract
Description
Technical Field
[0001] This invention belongs to the field of energetic materials technology, specifically relating to a nanocomposite aluminothermic agent composed of gallium-aluminum alloy and three-dimensional porous oxide, its preparation method, and its application. Background Technology
[0002] Thermite is a composite energetic material composed of fuel and oxidant, capable of undergoing a vigorous redox reaction and releasing a large amount of heat under certain excitation conditions. Aluminum, magnesium, silicon, and other elemental materials can all be used as fuels, with aluminum powder being the preferred choice due to its low price and high calorific value. Oxidants are mainly metal oxides such as iron oxide (Fe₂O₃), copper oxide (CuO), and molybdenum oxide (MoO₃). Numerous studies have shown that reducing the micron-sized components of thermite to the nanoscale can significantly increase the heat release and reduce the ignition energy. Further research indicates that reducing the particle size of thermite components from the micron to the nanoscale, as well as through component control (additives, alloying, etc.) or special structural designs (multilayer structures, porous structures, three-dimensional arrays, and core-shell structures), can effectively improve the performance of thermite. However, nano-aluminum presents challenges in processing and the large-scale supply of nano-aluminum powder. Furthermore, compared to micron-sized aluminum, nano-aluminum particles are more prone to oxidation during the preparation and subsequent storage of thermite, forming a dense, passivated alumina shell that hinders the reaction between the internal aluminum core and the oxidant, resulting in the thermite's performance not being fully realized in practical applications. Summary of the Invention
[0003] To overcome the shortcomings and deficiencies of the existing technologies mentioned above, which cannot fully meet the requirements of easy oxidation of nano-sodium and precise control of the uniformity and dispersion of aluminothermic components, the primary objective of this invention is to provide a method for preparing a nanocomposite aluminothermic agent composed of gallium-aluminum alloy and three-dimensional porous oxide. This method develops a novel aluminothermic agent through component regulation and structural design. By introducing liquid gallium metal, the formation of a complete and uniform Al2O3 passivation layer on the surface of aluminum fuel is suppressed. At the same time, the confinement effect of different three-dimensional porous oxidants is combined to protect the activity of nano-aluminum, enhance the contact degree of aluminothermic components and shorten the mass transfer diffusion length, thereby obtaining a high-performance aluminum-gallium-based nanocomposite aluminothermic agent.
[0004] Another objective of this invention is to provide a nanocomposite aluminothermic agent composed of gallium-aluminum alloy and three-dimensional porous oxide prepared by the above-described preparation method.
[0005] Another object of the present invention is to provide the application of the above-mentioned nanocomposite aluminothermic agent composed of gallium aluminum alloy and three-dimensional porous oxide.
[0006] The objective of this invention is achieved through the following technical solution:
[0007] A method for preparing a nanocomposite thermite composed of gallium-aluminum alloy and three-dimensional porous oxide includes the following steps:
[0008] (1) Liquid gallium metal is placed in a sealed container, and aluminum foil with the surface oxide film removed by polishing is added to the liquid gallium metal under the protection of an inert atmosphere. Then, the mixture is heated to react and a low melting point gallium-aluminum alloy is prepared. The mass ratio of gallium to aluminum in the low melting point gallium-aluminum alloy is in the range of 1:2 to 2:1.
[0009] (2) Preparation of three-dimensional ordered macroporous oxides by colloidal crystal template method: The dispersion of monodisperse polymer colloidal microspheres is self-assembled into a three-dimensional ordered macroporous colloidal crystal framework by vacuum filtration. Then, metal salts are impregnated into the pores of the three-dimensional ordered macroporous colloidal crystal framework by solution impregnation. After calcination at 300-500℃ for 5-10h in air atmosphere, the colloidal template decomposes and the metal salts are pyrolyzed and oxidized to obtain the corresponding three-dimensional ordered macroporous oxides; the metal salts are copper salts, zinc salts or cobalt salts.
[0010] (3) Preparation of three-dimensional porous oxide foil by dealloying method: using copper alloy foil or molybdenum alloy foil as template, wherein the copper alloy foil is an alloy of copper with at least one of the active components Zn, Mn and Mg, and the molybdenum alloy foil is an alloy of molybdenum with at least one of the active components Zn, Mn and Mg; the copper alloy foil or molybdenum alloy foil is immersed in dilute acid solution for 12-24h to dissolve and remove the active components therein, thereby obtaining a three-dimensional continuous porous copper or molybdenum skeleton with adjustable pore type and size, and then the surface of the three-dimensional continuous porous copper or molybdenum skeleton is oxidized by heat treatment at 300-500℃ in air atmosphere for 1-5h to form a layer of copper oxide or molybdenum trioxide to form a three-dimensional porous oxide foil;
[0011] (4) The low melting point gallium aluminum alloy obtained in step (1) and the three-dimensional ordered macroporous oxide obtained in step (2) are mixed and heated in an argon atmosphere. After heat treatment at 200-300℃, the low melting point gallium aluminum alloy is melted into a liquid state and injected into the three-dimensional ordered macroporous oxide obtained in step (2), thereby realizing the composite of gallium aluminum alloy fuel and three-dimensional ordered macroporous oxide, and obtaining a nanocomposite aluminothermic agent composed of gallium aluminum alloy and three-dimensional porous oxide.
[0012] (5) Stack the three-dimensional porous oxide foil obtained in step (3) and the low-melting-point gallium aluminum alloy obtained in step (1) on a flat plate heater. After heating at 200-300°C, the low-melting-point gallium aluminum alloy is melted into a liquid state and injected into the three-dimensional porous oxide foil to achieve the composite of gallium aluminum alloy fuel and three-dimensional porous oxide foil, thereby obtaining a nanocomposite aluminothermic agent composed of gallium aluminum alloy and three-dimensional porous oxide.
[0013] The inert gas mentioned in step (1) is argon; the temperature range of the heating reaction is 200-300℃, and the time range is 3-5h.
[0014] The melting point of the low-melting-point gallium-aluminum alloy mentioned in step (1) is ≤300℃.
[0015] The monodisperse polymer colloidal microspheres mentioned in step (2) are monodisperse polystyrene (PS) colloidal microspheres or polymethyl methacrylate (PMMA) microspheres; the solid content of the monodisperse polymer colloidal microsphere dispersion is 10 wt%; the volume range of the monodisperse polymer colloidal microsphere dispersion is 10-60 ml; and the size of the monodisperse polymer colloidal microspheres is 50-500 nm.
[0016] The solution impregnation method described in step (2) involves preparing a metal salt solution with a concentration of 0.05-0.2 mol / L for impregnation.
[0017] The dilute acid solution mentioned in step (3) is 0.5-1 mol / L hydrochloric acid.
[0018] A nanocomposite aluminothermic agent composed of gallium-aluminum alloy and three-dimensional porous oxide, prepared by the above-described method.
[0019] The above-mentioned nanocomposite aluminothermic agent composed of gallium aluminum alloy and three-dimensional porous oxide has applications in national defense and military industries and micro-motor systems.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] (1) Gallium-aluminum based alloys used in aluminothermic components can alter the microstructure of aluminum and partially transform the Al-Al interface into an Al-Ga interface, thereby suppressing the formation of a complete and uniform Al2O3 passivation layer on the surface. This can prevent the aluminum fuel from being oxidized during handling and storage, and can also accelerate the participation of aluminum in the reaction, thereby improving the reactivity of aluminum. On the other hand, the low-melting-point alloy formed by room-temperature liquid gallium (melting point of only 29.76℃) and aluminum can melt into a liquid state during heating at a relatively low temperature. Under the spatial confinement effect of the three-dimensional porous oxidant during the melt infusion process, the size of the aluminum fuel can be effectively suppressed, and the aggregation of nano-aluminum can be prevented in the subsequent process.
[0022] (2) Compared with vacuum physical vapor deposition, melt injection method is conducive to achieving higher nano-aluminum fuel loading and enhancing the contact between reactants; at the same time, it avoids the need for complex instruments or harsh reaction conditions that are usually required to produce highly reactive nano-aluminum, making it very suitable for large-scale production.
[0023] (3) Based on the advantages of gallium-aluminum alloy and three-dimensional porous oxidant, the present invention is expected to achieve a nanocomposite thermite with rapid and thorough combustion and explosion reaction, long-term storage, simple preparation process and low cost. Attached Figure Description
[0024] Figure 1 The image shows a SEM image of the nanocomposite aluminothermic material prepared in Example 1. Detailed Implementation
[0025] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto.
[0026] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; the materials and reagents used are commercially available unless otherwise specified.
[0027] Example 1
[0028] (1) Place 0.5g of liquid gallium metal in a sealed flask, and under the protection of argon gas, add 0.5g of aluminum foil with the surface oxide film removed by polishing to the above liquid gallium metal. Then heat the sealed flask to 200℃ and keep it at the temperature for 5h to prepare a low melting point (≤300℃) gallium-aluminum alloy.
[0029] (2) 10 ml of 10 wt% monodisperse polystyrene (PS) colloidal microsphere dispersion was filtered and self-assembled into a three-dimensional ordered macroporous colloidal crystal framework. The copper precursor copper nitrate was immersed into the pores of the three-dimensional ordered macroporous colloidal crystal framework by solution impregnation (the solution contained 30 mmol copper nitrate, 20 mmol citric acid, 6.5 ml ethylene glycol, and 3.5 ml methanol). After calcination in air at 300 °C for 8 h, the colloidal template was decomposed and the metal salt was pyrolyzed and oxidized to obtain the corresponding three-dimensional ordered macroporous CuO oxidant.
[0030] (3) Take 50 mg of the low-melting-point gallium-aluminum alloy obtained in step (1) and 5 mg of the three-dimensional ordered macroporous CuO oxidant obtained in step (2) and mix and heat them in an argon-atmosphere glove box. After heating to 200-300℃, the low-melting-point gallium-aluminum alloy melts into a liquid state and is then injected into the three-dimensional ordered macroporous CuO oxidant, thereby realizing the composite of gallium-aluminum alloy fuel and three-dimensional porous oxidant, and obtaining a nanocomposite thermite material composed of gallium-aluminum alloy and three-dimensional porous oxide. The SEM of this material is as follows: Figure 1 As shown.
[0031] Example 2
[0032] (1) Place 1g of liquid gallium metal in a sealed flask, and under the protection of argon gas, add 0.5g of aluminum foil with the surface oxide film removed by polishing to the above liquid gallium metal. Then heat the sealed flask to 300℃ and keep it at the temperature for 3h to prepare a low melting point (≤300℃) gallium-aluminum alloy.
[0033] (2) After filtering 30 ml of 10 wt% monodisperse polystyrene (PS) colloidal microsphere dispersion, it self-assembled into an ordered three-dimensional colloidal crystal framework. The copper precursor copper nitrate was immersed into the pores of the three-dimensional ordered macroporous colloidal crystal framework by solution impregnation (the solution contained 10 mmol copper nitrate, 20 mmol citric acid, 6.5 ml ethylene glycol, and 3.5 ml methanol). After calcination in air at 500 °C for 7.5 h, the colloidal template was decomposed and the metal salt was pyrolyzed and oxidized to obtain the corresponding three-dimensional ordered macroporous CuO oxidant.
[0034] (3) Take 45 mg of the low-melting-point gallium-aluminum alloy obtained in step (1) and 7 mg of the three-dimensional ordered macroporous CuO oxidant obtained in step (2) and mix and heat them in a glove box under an argon atmosphere. After heating to 200-300℃, the low-melting-point gallium-aluminum alloy melts into a liquid state and is then injected into the three-dimensional ordered macroporous CuO oxidant, thereby realizing the composite of gallium-aluminum alloy fuel and three-dimensional porous oxidant. A nanocomposite thermite material composed of gallium-aluminum alloy and three-dimensional porous oxide is obtained.
[0035] Example 3
[0036] (1) Place 0.5g of liquid gallium metal in a sealed flask, and under the protection of argon gas, add 1g of aluminum foil with the surface oxide film removed by polishing to the above liquid gallium metal. Then heat the sealed flask to 200℃ and keep it at the temperature for 5h to prepare a low melting point (≤300℃) gallium-aluminum alloy.
[0037] (2) The Cu-Mn alloy foil was immersed in 1 mol / L hydrochloric acid for 24 h to etch and dissolve and remove the active components to obtain a three-dimensional continuous porous copper skeleton with adjustable pore type and size. After taking it out, it was cleaned with deionized water and calcined at 400℃ for 1 h in air atmosphere to oxidize the surface of the three-dimensional continuous porous copper skeleton to form a layer of copper oxide to form a three-dimensional porous CuO oxidant foil.
[0038] (3) Take 50mg of the low melting point gallium aluminum alloy obtained in step (1) and the three-dimensional porous CuO oxidant foil obtained in step (2) and place them in a glove box under an argon atmosphere. Stack the three-dimensional porous CuO oxidant foil and the low melting point gallium aluminum alloy on a flat heater. After heating to 200-300℃, the low melting point gallium aluminum alloy melts into a liquid state and is injected into the three-dimensional porous CuO oxidant foil, thereby realizing the composite of gallium aluminum alloy fuel and three-dimensional porous oxidant, and obtaining a nanocomposite aluminothermic material composed of gallium aluminum alloy and three-dimensional porous oxide.
[0039] Example 4
[0040] (1) Place 0.5g of liquid gallium metal in a sealed flask, and under the protection of argon gas, add 1g of aluminum foil with the surface oxide film removed by polishing to the above liquid gallium metal. Then heat the sealed flask to 200℃ and keep it at the temperature for 5h to prepare a low melting point (≤300℃) gallium-aluminum alloy.
[0041] (2) The Cu-Zn alloy foil was immersed in 1 mol / L hydrochloric acid for 24 h to etch and dissolve and remove the active components to obtain a three-dimensional continuous porous copper skeleton with adjustable pore type and size. After that, it was taken out and cleaned with deionized water. It was then calcined at 400℃ for 1 h in air atmosphere to oxidize the surface of the three-dimensional continuous porous copper skeleton to form a layer of copper oxide and form a three-dimensional porous CuO oxidant foil.
[0042] (3) Take 50mg of the low melting point gallium aluminum alloy obtained in step (1) and the three-dimensional porous CuO oxidant foil obtained in step (2) and place them in a glove box under an argon atmosphere. Stack the three-dimensional porous CuO oxidant foil and the low melting point gallium aluminum alloy on a flat heater. After heating to 200-300℃, the low melting point gallium aluminum alloy melts into a liquid state and is injected into the three-dimensional porous CuO oxidant, thereby realizing the composite of gallium aluminum alloy fuel and three-dimensional porous oxidant, and obtaining a nanocomposite aluminothermic material composed of gallium aluminum alloy and three-dimensional porous oxide.
[0043] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A method for preparing a nanocomposite thermite composed of gallium-aluminum alloy and three-dimensional porous oxide, characterized in that... The following steps are included: (1) Liquid gallium metal is placed in a sealed container, and aluminum foil with the surface oxide film removed by polishing is added to the liquid gallium metal under the protection of an inert atmosphere. Then, the mixture is heated to prepare a low melting point gallium-aluminum alloy. The mass ratio of gallium to aluminum in the low melting point gallium-aluminum alloy is in the range of 1:2 to 2:
1. (2) Preparation of three-dimensional ordered macroporous oxides by colloidal crystal template method: The dispersion of monodisperse polymer colloidal microspheres is self-assembled into a three-dimensional ordered macroporous colloidal crystal framework by vacuum filtration. Then, metal salts are impregnated into the pores of the three-dimensional ordered macroporous colloidal crystal framework by solution impregnation. After calcination at 300-500℃ for 5-10 h in air atmosphere, the colloidal template decomposes and the metal salts are pyrolyzed and oxidized to obtain the corresponding three-dimensional ordered macroporous oxides; the metal salts are copper salts, zinc salts or cobalt salts. (3) Preparation of three-dimensional porous oxide foil by dealloying method: using copper alloy foil or molybdenum alloy foil as template, wherein the copper alloy foil is an alloy of copper with at least one of the active components Zn, Mn and Mg, and the molybdenum alloy foil is an alloy of molybdenum with at least one of the active components Zn, Mn and Mg. The copper alloy foil or molybdenum alloy foil is immersed in a dilute acid solution for 12-24 hours to dissolve and remove the active components, resulting in a three-dimensional continuous porous copper or molybdenum skeleton with adjustable pore type and size. Then, the surface of the three-dimensional continuous porous copper or molybdenum skeleton is oxidized by heat treatment at 300-500℃ in air atmosphere for 1-5 hours to form a layer of copper oxide or molybdenum trioxide, thus forming a three-dimensional porous oxide foil. (4) The low melting point gallium aluminum alloy obtained in step (1) and the three-dimensional ordered macroporous oxide obtained in step (2) are mixed and heated in an argon atmosphere. After heat treatment at 200-300℃, the low melting point gallium aluminum alloy is melted into a liquid state and injected into the three-dimensional ordered macroporous oxide obtained in step (2), thereby realizing the composite of gallium aluminum alloy fuel and three-dimensional ordered macroporous oxide, and obtaining a nanocomposite aluminothermic agent composed of gallium aluminum alloy and three-dimensional porous oxide. (5) Stack the three-dimensional porous oxide foil obtained in step (3) and the low-melting-point gallium aluminum alloy obtained in step (1) on a flat plate heater. After heating at 200-300°C, the low-melting-point gallium aluminum alloy is melted into a liquid state and injected into the three-dimensional porous oxide foil to achieve the composite of gallium aluminum alloy fuel and three-dimensional porous oxide foil, and obtain a nanocomposite aluminothermic agent composed of gallium aluminum alloy and three-dimensional porous oxide.
2. The method for preparing a nanocomposite aluminothermic agent composed of gallium-aluminum alloy and three-dimensional porous oxide according to claim 1, characterized in that: The inert atmosphere mentioned in step (1) is argon; the temperature range of the heating reaction is 200-300℃, and the time range is 3-5h.
3. The method for preparing a nanocomposite aluminothermic agent composed of gallium-aluminum alloy and three-dimensional porous oxide according to claim 1, characterized in that: The melting point of the low-melting-point gallium-aluminum alloy mentioned in step (1) is ≤300 ℃; 4. The method for preparing a nanocomposite aluminothermic agent composed of gallium-aluminum alloy and three-dimensional porous oxide according to claim 1, characterized in that: The monodisperse polymer colloidal microspheres in step (2) are monodisperse polystyrene colloidal microspheres or polymethyl methacrylate microspheres; the solid content of the monodisperse polymer colloidal microsphere dispersion is 10 wt%; the volume range of the monodisperse polymer colloidal microsphere dispersion is 10-60 ml; and the size of the monodisperse polymer colloidal microspheres is 50-500 nm.
5. The method for preparing a nanocomposite aluminothermic agent composed of gallium-aluminum alloy and three-dimensional porous oxide according to claim 1, characterized in that: The solution impregnation method described in step (2) involves preparing a metal salt solution with a concentration of 0.05-0.2 mol / L for impregnation.
6. The method for preparing a nanocomposite aluminothermic agent composed of gallium-aluminum alloy and three-dimensional porous oxide according to claim 1, characterized in that: The dilute acid solution mentioned in step (3) is 0.5-1 mol / L hydrochloric acid.
7. A nanocomposite aluminothermic agent composed of gallium-aluminum alloy and three-dimensional porous oxide, prepared by the preparation method according to any one of claims 1 to 6.
8. The application of the nanocomposite aluminothermic agent composed of gallium aluminum alloy and three-dimensional porous oxide as described in claim 7 in national defense and military industries and micro-motor systems.
Citation Information
Patent Citations
Nanometer thermite and preparing method thereof
CN105177517A
Method for preparing nano aluminum / porous copper oxide nano thermite through P4VP self-assembly
CN112920001A